Vascular-adhesion protein 1 in giant cell arteritis and polymyalgia rheumatica - Petzinna, Simon M.; Bauer, Claus-Jürgen; Schäfer, Valentin S. (Frontiers in Medicine, 2024)
Vascular adhesion protein-1 (VAP-1) is a type 2 transmembrane sialoglycoprotein with oxidative deamination functionality, encoded by the amine oxidase copper-containing 3 (AOC3) gene. VAP-1 is widely expressed across various tissues, particularly in highly vascularized tissues and organs essential for lymphocyte circulation. In the vascular system, VAP-1 is predominantly found in vascular smooth muscle cells and endothelial cells, with higher expression levels in vascular smooth muscle cells. Under inflammatory conditions, VAP-1 rapidly translocates to the endothelial cell surface, facilitating leukocyte adhesion and migration through interactions with specific ligands, such as sialic acid-binding immunoglobulin-type lectins (Siglec)-9 on neutrophils and monocytes, and Siglec-10 on B cells, monocytes, and eosinophils. This interaction is crucial for leukocyte transmigration into inflamed tissues. Furthermore, VAP-1’s enzymatic activity generates hydrogen peroxide and advanced glycation end-products, contributing to cytotoxic damage and vascular inflammation. In this context, the soluble form of VAP-1 (sVAP-1), produced by matrix metalloproteinase cleavage from its membrane-bound counterpart, also significantly influences leukocyte migration. This review aims to elucidate the multifaceted pathophysiological roles of VAP-1 in vascular inflammation, particularly in giant cell arteritis (GCA) and associated polymyalgia rheumatica (PMR). By exploring its involvement in immune cell adhesion, migration, and its enzymatic contributions to oxidative stress and tissue damage, we investigate the importance of VAP-1 in GCA. Additionally, we discuss recent advancements in imaging techniques targeting VAP-1, such as [68Ga]Ga-DOTA-Siglec-9 PET/CT, which have provided new insights into VAP-1’s role in GCA and PMR. Overall, understanding VAP-1’s comprehensive roles could pave the way for improved strategies in managing these conditions.